(untitled) (Cambridge [England], 1998)
The book is divided into sections on Culture as Text and Code, The Production and Reception of Culture, and Culture in Action, each containing edited theoretical and empirical contributions that address the key debates in cultural sociology: the autonomy of culture, power and culture, structure and agency, and the concept of meaning.
Keywords: Culture,Văn hóa; Research,Nghiên cứu; United States,Hoa Kỳ